Modeling moist air effects and shape memory alloys in elastocaloric devices - Zimmermann, D.; Louia, F.; Welsch, F.; Motzki, P.; Seelecke, S. (Frontiers in Materials, 2025)
Elastocaloric systems, which leverage shape memory alloys (SMAs) to achieve efficient, eco-friendly thermal management, offer a promising alternative to conventional air conditioning technologies. This study presents a simulation-based approach to modeling the effects of moist air and condensation phenomena within these systems. Here, we examine key factors affecting SMA performance, including mechanical behavior and the material’s latent heat characteristics. Moist air, particularly under conditions where temperatures fall below the dew point, introduces condensation and latent heat release, which can influence thermal output in elastocaloric systems. This work develops a comprehensive model that couples the thermomechanical behavior of SMAs with the thermodynamics of moist air, incorporating condensation heat transfer, mass balance, and moisture transport. Through simulations, we quantify the impact of condensation on device level and assess how ambient moisture conditions affect overall heat exchange. The findings enhance our understanding of elastocaloric system performance under real-world conditions, contributing to the advancement of sustainable and modern technologies.